Ethiopian agriculture: A dynamic geographic perspective - Chamberlin, Jordan; Schmidt, Emily (International Food Policy Research Institute, 2011)
The opportunities and constraints facing Ethiopian agriculture are strongly influenced by conditions which vary across geographical space. These conditions include basic agricultural production potentials, access to input and output markets, and local population densities which represent both labor availability and local demand for food. Understanding the geographical expression of these factors is an important way of making sense of Ethiopia's agricultural and rural development options and for guiding the definition of supporting policies.